ACTIVATION FUNCTIONS IN NEURAL NETWORKS: A COMPREHENSIVE OVERVIEW - Sudeep Meduri , (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores the critical role of activation functions in neural networks, elucidating their significance in enabling non-linear transformations, controlling output ranges, and facilitating complex function approximation. The article examines various activation functions, including sigmoid, tanh, ReLU, and their variants, analyzing their properties, advantages, and limitations. It discusses the impact of activation functions on neural network design, including their influence on network depth, initialization strategies, learning rates, and regularization techniques. The article provides insights into choosing appropriate activation functions based on problem type, network architecture, and empirical performance. Recent advancements, such as adaptive and learnable activation functions, are also explored. By offering a thorough analysis of how activation functions shape the behavior and capabilities of neural networks, this review equips readers with the knowledge to make informed decisions when designing and optimizing machine learning models for diverse applications. The ongoing importance of activation function research in advancing deep learning is emphasized, with potential future developments including more context-dependent functions and dynamic selection mechanisms. This article underscores the fundamental role of activation functions in pushing the boundaries of artificial intelligence and machine learning capabilities.